Peran dukungan pasangan dan keyakinan diri mengelola konflik kerja-keluarga terhadap konflik kerja-keluarga selama work fromhome pada dosen wanita yang sudah menikah - Andhini, Luh Putu Ratih; Utami, Ni Made Sintya Noviana; Dewi, Anak Agung Dyah Pramudya; Shantiyani, I Gusti Ayu Yurika Wahyuning (Jurnal Psikologi Udayana; Vol 8 No 2 (2021), 2021)
Work-family conflict have been strongly felt by married female lecturers in the midst of the Covid-19 virus pandemic. Lecturers must carry out their duties from home, besides that they also have the task of taking care of children and husbands at home. Work-family conflict can be affected by work family conflict self-efficacy and spouse support. The purpose of this study was to see the relationship between the two variables (work-family conflict self-efficacy and spouse support) simultaneously on work-family conflict in married female lecturers. Subject totaled 21 female lecturers who worked as lecturers at a university. Researchers used the work family conflict, the work family conflict self-efficacy, and spouse support scale. The results obtained by R square = 0.428 means that work-family conflict self-efficacy and spouse support has a role as much as 42.8% in explaining work-family conflict. R value = 0.654; F = 6737; and p = 0.007 ?<0.05 where the hypothesis is accepted, meaning that there is a significant role between work-family conflict, self-efficacy, and spouse support for work-family conflict in married female lecturers at University X during work from home. The Beta value shows that spouse support has a higher value that affects work-family conflict than work-family conflict self-efficacy.